103 A Review of Reviews of Emergency Department Interventions for Older People: Outcomes, Costs and Implementation Factors. (6th February 2020) - van Oppen, J; Preston, L; Ablard, S; Buckley Woods, H; Mason, S; Conroy, S
Abstract: Introduction: Older people's emergency care is an international public health priority and remains sub-optimal in the UK. Strategies are needed to manage older patients sensitively and effectively. We reviewed emergency care interventions, evaluating evidence for outcomes, costs, and implementation. Methods: We developed and registered (with PROSPERO, CRD42018111461) a review of reviews protocol. Screening was according to inclusion criteria for subject and reporting standards. Data were extracted and summarised in tabular and narrative form. Quality was assessed using AMSTAR2 and Joanna Briggs Institute tools. Due to intervention and outcome heterogeneity, findings were synthesised narratively. McCusker's Elder-Friendly Emergency Department assessment tool was used as a classification framework. Results: Eighteen review articles and three conference abstracts fulfilled inclusion criteria. The majority were systematic reviews, with four using meta-analysis. Fourteen reviews reported interventions initiated or wholly delivered within the ED, and four focussed on quality indicators or patient preferences. Confidence was limited to each review's interpretation of primary studies. Descriptions of interventions were inconsistent, and there was high variability in reporting standards. Interventions mostly focussed on screening and assessment, discharge planning, referrals and follow-up, and multi-disciplinary team composition and professional activities. 26 patient and health service outcomes were reported, including admissions and readmissions, length of stay, mortality, functional decline, and quality of life. Conclusions: Our review of reviews demonstrated that the current, extensive evidence base of review studies lacks complexity, with limited or no evidence for the effectiveness of interventions; reviews commonly called for more primary research using rigorous methods. There is little review evidence for factors influencing implementation. There was evidence that among interventions initiated in ED, those continued into the community yielded better outcomes. Service metrics (as valued by care commissioners) were evaluated as intervention outcomes more frequently than person-centred attributes (as valued by older people). Interventions were broadly holistic in nature.